Effects of Intranasal and Oral Bordetella bronchiseptica Vaccination on the Behavioral and Olfactory Capabilities of Detection Dogs - Collins, Amanda; Bear, Rachel A.; Mallikarjun, Amritha; Kane, Sarah A.; Essler, Jennifer L.; Kaynaroglu, Patricia; Feuer, Rebecca; Smith, Jordan G.; Otto, Cynthia M. (Frontiers in Veterinary Science, 2022)
The bacterium Bordetella bronchiseptica is responsible for serious respiratory disease in dogs, most often associated with ‘kennel cough’ (canine infectious tracheobronchitis). It is recommended that dogs are vaccinated against the bacterium every 6-12 months, either by oral or intranasal administration. The intranasal vaccine may cause inflammation of the nasal mucosal epithelium because of the immune response to the vaccine. Any impairment of dogs’ olfactory capabilities due to medical treatments may impact their efficiency and accuracy in their jobs. The first study compared the effect of intranasal versus oral vaccine on the olfactory capabilities of sixteen detection dogs. Olfactory acuity was based on odor threshold and behavior during search was scored using an ethogram identifying behaviors associated with either positive or negative motivation. Dogs that were vaccinated initially with the oral and 28 days later with intranasal B. bronchiseptica were generally slower to find the target odor than the dogs that were assigned intranasal then oral vaccine. Since there was an order effect, a second study used a between-subjects designed to further investigate any impact of intranasal administration of the B. bronchiseptica vaccine on the olfactory capabilities of dogs. Neither odor threshold nor time spent searching for odor were affected by intranasal vaccination for B. bronchiseptica. Odor detection is influenced by both olfaction and search behavior. Behavioral analyses showed that behaviors associated with the dogs’ positive and negative motivation affected their time spent finding the target odor; this suggests that behavior should be considered in future studies of olfactory performance.